2012
DOI: 10.1111/j.1740-1461.2012.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Medicine and Obstetric Practices

Abstract: Using data on physician behavior from the 1979–2005 National Hospital Discharge Surveys (NHDS), I estimate the relationship between malpractice pressure, as identified by the adoption of noneconomic damage caps and related tort reforms, and certain decisions faced by obstetricians during the delivery of a child. The NHDS data, supplemented with restricted geographic identifiers, provides inpatient discharge records from a broad enough span of states and covering a long enough period of time to allow for a defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
0
43
2
Order By: Relevance
“…Currie and MacLeod () challenged this common idea that higher malpractice pressure induces obstetricians to perform excessive C‐sections, and they provided contrasting evidence. As already suggested by other studies (Sloan et al , ; Dubay et al , ; Frakes, ), they showed that higher malpractice pressure does not necessarily lead to a more frequent use of C‐sections. The finding of Currie and MacLeod () is consistent with a model of doctor behavior that depends on both patient conditions and the probability of committing an error with potential legal consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Currie and MacLeod () challenged this common idea that higher malpractice pressure induces obstetricians to perform excessive C‐sections, and they provided contrasting evidence. As already suggested by other studies (Sloan et al , ; Dubay et al , ; Frakes, ), they showed that higher malpractice pressure does not necessarily lead to a more frequent use of C‐sections. The finding of Currie and MacLeod () is consistent with a model of doctor behavior that depends on both patient conditions and the probability of committing an error with potential legal consequences.…”
Section: Introductionmentioning
confidence: 99%
“…12,16,[27][28][29][30]32,[34][35][36]38,40,[42][43][44][45][46] Twelve studies evaluated the impact of tort reform on defensive medicine by assessing health care utilization 20,22,23,25,26,28,37,38,47,49,51,52 of which two (17 percent) used a difference-in-differences specification. 28,38 Thirteen studies studied quality of care 16,20,21,26,28,29,[33][34][35]37,41,48,54 of which five (38 percent) used a difference-in-differences specification. 16,28,29,34,35 Health care spending was evaluated by eight studies…”
Section: Study Characteristicsmentioning
confidence: 99%
“…28,38 Thirteen studies studied quality of care 16,20,21,26,28,29,[33][34][35]37,41,48,54 of which five (38 percent) used a difference-in-differences specification. 16,28,29,34,35 Health care spending was evaluated by eight studies 12,16,20,31,35,43,44,48 of which five (63 percent) used a difference-in-differences specification. 12,16,35,43,44 Thirteen studies evaluated the association of tort reform with physician supply 24,27,30,32,34,36,39,40,42,45,46,50,53 of which nine (69 percent) used a difference-in-differences specification.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations